Design Analysis and Implementation of Parallel Working Arm of Heavy Duty Pouring Robot - Chengke Xu; Chengjun Wang; Yongcun Guo; Long Li; Lüzhong Ma (Jixie chuandong)
In order to solve the problems of low load， low flexibility and low precision in the pouring operations of serial robots widely used in foundry production， a new type of hybrid heavy-duty pouring robot is proposed. A three-degree-of-freedom parallel working arm based on 2UPR-2RPU mechanism is designed，the topology analysis and degrees of freedom calculation are carried out. By establishing the kinematics model and statics model of the parallel working arm， the variation law of the length of the mechanism branch with the angle of the pouring ladle is analyzed. The relationship between the condition of the branch and the stroke size and the position of the branch on the static platform is analyzed. The structure and parameters of the parallel working arm are optimized. For a ladle of 300 kg， a set of structural parameters with better comprehensive properties is selected out. After prototype trial production and testing， the results show that the design proposal and structural parameters of the parallel working arm are reasonable.